Non-Gaussian tail in the force distribution: a hallmark of correlated disorder in the host media of elastic objects - Sanchez, J.A.; Rumi, G.; Cortés Maldonado, R.; Cejas Bolecek, N.R.; Puig, J.; Pedrazzini, P.; Nieva, G.; Dolz, M.I.; Konczykowski, M.; van der Beek, C.J.; Kolton, A.B.; Fasano, Y.; et al. (Springer Nature, 2020)
Fil: Sanchez, J.A. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina